THE PROTECTIVE EFFECTS OF TETRANDRINE AGAINST TO HISTOLOGICAL, SPERMATOLOGICAL AND OXIDATIVE DAMAGE INDUCED BY AROCLOR 1254 ON THE MALE RATS REPRODUCTIVE SYSTEM - Feride Özdemir; Aslı Çetin Taşlıdere; Osman Çiftçi; Muhterem Aydın; Neşe Başak Türkmen (Sabiad)
Objectives: Aroclor (AR) 1254; has many adverse effects on male reproduction such as carcinogenic, teratogenic, immune and endocrine disruption problems. Tetrandrine (TET), a bisbenzillisoquinoline alkaloid isolated from the root of Stephania tetrandra S. Moore, has protective effects such as immunomodulatory, anti-cancer, and anti-inflammatory. The objective of this study was to investigate the possible curative effects of TET therapy against testicular damage (histological, spermatological and oxidative damage) induced by AR1254. Materials and Methods: Twenty-eight male rats were randomly divided into four equal-sized groups: a control group; (1 ml of corn oil by gastric oral gavage), AR1254 group; (2 mg/kg) AR1254 administered intraperitoneally), TET group; (TET by gastric oral gavage 30 mg/kg) and AR 1254 + TET group;(Aroclor 1254 and TET administered together at the same doses as the previous groups. Results: The AR1254 treatment caused morphological and spermatological damage on testis tissue; oedema vacuolization and congestion, in interstitial area, reduction in spermatogenic cells, arrested spermatocytes at different stages of spermatogenesis, shedding of spermatogenic serial cells into tubular lumens, a decline in epididymal sperm concentrations, sperm motility and a rise in abnormal sperm ratios. The AR1254 administration induced an increase in the oxidative parameters and a decrease in enzymatic and nonenzymatic antioxidant levels. The TET treatment significantly ameliorated histological, oxidative, and sperm damage caused by AR1254. Conclusion: This study demonstrated the protective effects of TET against AR1254-induced male rat reproductive damage.